Lifetime sexual violence exposure in women compromises systemic innate immune mediators associated with HIV pathogenesis: A cross-sectional analysis. (May 2022) - Daniels, Jason; Aldous, Annette; Pyra, Maria; Xia, Yu; Juzumaite, Monika; Jais, Mariel; Simmens, Samuel; Murphy, Kerry; Taylor, Tonya N; Kassaye, Seble; Benning, Lorie; Cohen, Mardge H; et al.
Objectives: Violence and HIV/AIDS syndemic highly prevalent among women impairs HIV prevention efforts. Prolonged exposure to violence results in physical trauma and psychological distress. Building on previous findings regarding genital immune dysregulation following sexual abuse exposure, we investigate here whether systemic changes occur as well. Methods: Using the Women's Interagency HIV Study repository, 77 women were stratified by HIV serostatus and categorized into four subgroups: (1) no sexual abuse history and lower depression score (Control); (2) no sexual abuse history but higher depression score (Depression); (3) high sexual abuse exposure and lower depression score (Abuse); (4) high sexual abuse exposure and higher depression score (Abuse + Depression). Inflammation-associated immune biomarkers (TNF-α, IL-6, IL-1α, IL-1β, TGF-β, MIP-3α, IP-10, MCP-1, and Cathepsin-B) and anti-inflammatory/anti-HIV biomarkers (Secretory leukocyte protease inhibitor, Elafin, human beta-defensin-2 (HBD-2), alpha-defensins 1-3, Thrombospondin, Serpin-A1, and Cystatin-C) were measured in plasma using enzyme-linked immunosorbent assay. Within each HIV serostatus, differences in biomarker levels between subgroups were evaluated with Kruskal–Wallis and Dunn's test with Bonferroni correction. Spearman correlations between biomarkers were assessed for each subgroup. Results: Compared to the Control and Depression groups, Abuse + Depression was associated with significantly higher levels of chemokines MIP-3α and IP-10 (p < 0.01) and lower levels of inflammatory cytokine IL-1β (p < 0.01) in the HIV-uninfected population. Human beta-defensin-2 was lowest in the Abuse + Depression group (p < 0.05 versus Depression). By contrast, among HIV-infected, Abuse and Abuse + Depression were associated with lower levels of MIP-3α (p < 0.05 versus Control) and IP-10 (p < 0.05, Abuse versus Control). Inflammatory cytokine IL-6 was higher in both Abuse groups (p < 0.05 versus Control), while Elafin was lowest in the Abuse + Depression group (p < 0.01 versus Depression). Conclusion: We report compromised plasma immune responses that parallel previous findings in the genital mucosa, based on sexual abuse and HIV status. Systemic biomarkers may indicate trauma exposure and impact risk of HIV acquisition/transmission.